Heterodimerization with Its Splice Variant Blocks the Ghrelin Receptor 1a in a Non-signaling Conformation: A STUDY WITH A PURIFIED HETERODIMER ASSEMBLED INTO LIPID DISCS - Mary, Sophie (American Society for Biochemistry and Molecular Biology, 2013)
Heterodimerization of G protein-coupled receptors has an impact on their signaling properties, but the molecular mechanisms underlying heteromer-directed selectivity remain elusive. Using purified monomers and dimers reconstituted into lipid discs, we explored how dimerization impacts the functional and structural behavior of the ghrelin receptor. In particular, we investigated how a naturally occurring truncated splice variant of the ghrelin receptor exerts a dominant negative effect on ghrelin signaling upon dimerization with the full-length receptor. We provide direct evidence that this dominant negative effect is due to the ability of the non-signaling truncated receptor to restrict the conformational landscape of the full-length protein. Indeed, associating both proteins within the same disc blocks all agonist- and signaling protein-induced changes in ghrelin receptor conformation, thus preventing it from activating its cognate G protein and triggering arrestin 2 recruitment. This is an unambiguous demonstration that allosteric conformational events within dimeric assemblies can be directly responsible for modulation of signaling mediated by G protein-coupled receptors.